2020
DOI: 10.1101/2020.07.24.220111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heterogeneous genetic basis of age at maturity in salmonid fishes

Abstract: Understanding the genetic basis of repeated evolution of the same phenotype across taxa is a fundamental aim in evolutionary biology and has applications to conservation and management. However, the extent to which interspecific life-history trait polymorphisms share evolutionary pathways remains under-explored. We address this gap by studying the genetic basis of a key life-history trait, age at maturity, in four species of Pacific salmon (genus Oncorhynchus) that exhibit intra- and interspecific variation in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 124 publications
3
21
0
Order By: Relevance
“…The second strongest associated locus in this study is located in close proximity to six6 on ssa09. This locus was previously found to be associated with early maturation in male farmed Atlantic salmon [19], with sea age at maturity in wild Atlantic salmon prior to population structure correction [10] and two species of Pacific salmon (Sockeye salmon and Steelhead trout) [36]. Additionally, we found another three loci associated with sea age at maturity: pecam1, asap2aa and taar13c.…”
Section: Multi-snp Associations Identified Using Pimasssupporting
confidence: 69%
See 1 more Smart Citation
“…The second strongest associated locus in this study is located in close proximity to six6 on ssa09. This locus was previously found to be associated with early maturation in male farmed Atlantic salmon [19], with sea age at maturity in wild Atlantic salmon prior to population structure correction [10] and two species of Pacific salmon (Sockeye salmon and Steelhead trout) [36]. Additionally, we found another three loci associated with sea age at maturity: pecam1, asap2aa and taar13c.…”
Section: Multi-snp Associations Identified Using Pimasssupporting
confidence: 69%
“…The association of six6 was also found by Barson et al [10] in wild Atlantic salmon, however, the signal disappeared after correction for population structure. Interestingly, the six6 gene is also associated with age at maturity in two Pacific salmon species [36], humans [35] and cattle [37]. However, Barson et al [10] focused solely on single-SNP associations via GWAS without considering the possible influence of combined variant effects.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found areas of the genome other than that identified on chromosome 25 can be associated with sea age at maturation [41] whilst others have suggested vgll3 may work in synergy with other genes such as TEAD3 [42] and six6 [15]. In a study on six6 and vgll3 associations with age at maturity in four species of Pacific salmon, Walters et al 2020 [43] found a significant association between six6 and age at maturity in two species, but not for vgll3 in any species. Further work is required in order to understand the interplay between these genes in Atlantic salmon.…”
Section: Genotype and The Likelihood Of Jackingmentioning
confidence: 98%
“…In addition, the panel included thirteen markers in the region of chromosomes 28 associated with migration timing (Micheletti, Matala, et al, 2018), with six from exonic and intronic regions of the GREB1L gene, six from the intergenic region, and one from an intron of the ROCK1 gene (Table S1) (Collins et al, 2020). Finally, the panel included ten markers in the region of chromosome 25 associated with age and size in maturity (Waters et al, 2020) with three in the first transcribed region of the SIX6 gene, six in the upstream intergenic region, and one in the downstream intergenic region (Table S1).…”
Section: Genotypingmentioning
confidence: 99%
“…In contrast, a recent study of steelhead using whole‐genome resequencing data found a consistent signal of association only in the region of chromosome 25 containing the SIX6 gene among populations in the interior Columbia basin, Puget Sound (WA), and California, and developed several candidate genomic markers for age‐at‐maturity (C.D. Waters et al., 2020). This gene, which is known in humans to have effects on age‐at‐menarche as well as adult height (Perry et al., 2014), may influence age‐at‐maturity through adipogenesis and gametogenesis (Jean, Bernier, & Gruss, 1999; Kurko et al., 2019; Larder, Clark, Miller, & Mellon, 2011).…”
Section: Introductionmentioning
confidence: 98%